Manajemen Perancangan Taman Budaya Banglipuran, Melikan, Rongkop, Gunungkidul - Septiono Eko Bawono; Rizaldi Patria; Samsuharjo Samsuharjo (FEB Universitas Maritim Semarang, 2023)
Melikan Village area is part of Pegunungan Sewu area. This area is included in a national protected area and has been part of UNESCO's Global Geopark Network since 2015. As a karst areas, this area has potential natural resources, human resources, and socio-economic-culture. This research has mapped all of these potentials to become the basis for designing the Taman Budaya Banglipuran which is the focus of the development of the Melikan Village area. The approach used in this study is action research which is carried out in three stages. The research phase are: mapping, planning and development. The mapping is digital using Quantum GIS. Planning is carried out with FGD. And development includes area planning with 3D visuals. This research aims to assist the community in developing the Banglipuran area by producing area designs.